THE USE OF PRE-QUESTIONING TO IMOROVE STUDENTS’ READING COMPREHENSION - Mangare, Putri; Muntuuntu, Meity; Rombepajung, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to find out whether the pre-questioning is able to improve students' reading comprehension at SMA Negeri 1 Tondano. This research used quantitative research with a pre-experimental design. This study was applied in one group of pre-test, treatment, and post-test. The subject of this research was the eleventh-grade students of SMA Negeri 1 Tondano. The data collection that is used is an essay test that consists of 20 numbers. The writer used the mean score formula to analyse the data. The results showed that there was an increase in the scores achieved by students in the pre-test and post-test. The students' average score in the pre-test was 48.25, while the students' average score in the pre-test was 77.75. The results of this study indicate that the mean score from the post-test was 29.5% higher than the pre-test. These data show that the pre-questioning strategy is effective in improving students' reading comprehension in the eleventh grade of SMA Negeri 1 Tondano.